1999
DOI: 10.1159/000028859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrauterine Myelomeningocele Repair on Central Nervous System Structure and Function

Abstract: Background: It has been postulated that intrauterine myelomeningocele repair might improve neurologic outcome in patients with myelomeningocele. A total of 59 such procedures have been performed at Vanderbilt University. Preliminary results suggested that the degree of hindbrain herniation is reduced by intrauterine repair. In an attempt to further quantify the possible benefits of this surgery, a subset of these patients was brought back to Vanderbilt for study. Methods: A group of 26 patients who had undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 7 publications
0
64
1
1
Order By: Relevance
“…Other researchers have also used our method of comparison of gestational age based on last menstrual period with gestational age predicted from biometric measurements using Hadlock's tables 9,10 . One could also speculate that postnatal lower extremity growth measurements might be a potential outcome measure after fetal surgery for myelomeningocele 11,12 , given the absence of shortening of the femur in the second or third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also used our method of comparison of gestational age based on last menstrual period with gestational age predicted from biometric measurements using Hadlock's tables 9,10 . One could also speculate that postnatal lower extremity growth measurements might be a potential outcome measure after fetal surgery for myelomeningocele 11,12 , given the absence of shortening of the femur in the second or third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies examining open fetal surgery suggested considerable possibility of preterm labor and uterine dehiscence, as well as an increased risk of preterm delivery and fetal mortality. 19,20 Additional maternal and fetal risks include not only those from general and regional anesthesia during pregnancy, but also hemorrhage, infection, damage to adjacent organs, pulmonary edema, pulmonary embolism, oligohydramnios, chorioamniotic membrane separation, and need for fetal resuscitation. In a single institution retrospective review of 87 hysterotomies performed for fetal surgery between 1989 and 2003, 28% of mothers had pulmonary edema, 52% had premature rupture of membranes, 13% required blood products, 9% had chorioamnionitis, and the risk of preterm delivery was high and occurred at a mean gestational age of 30 weeks.…”
Section: The Development Of Fetal Surgerymentioning
confidence: 99%
“…12,27 Early studies looking at open in utero repair of myelomeningocele in humans suggested a reduction in hindbrain herniation, but risks to both the fetus and mother were apparent. 19,20 These findings led to the development and recent publication of an unmasked, randomized, prospective clinical trial examining the potential benefit of open fetal surgery, The Management of Myelomeningocele Study (MOMS). 28 The MOMS trial had the primary goal of determining the safety and efficacy of repairing neural tube defects in utero when compared to post-natal closure.…”
Section: Management Of Myelomeningocele (Moms) Trialmentioning
confidence: 99%
“…This often needs to be replaced as the child grows because of problems with blockage and infection. [53][54][55][56][57] The prognosis for babies born with OSB depends on the location, size and extent of the defect and the presence of hydrocephalus, and the range of disability caused is variable. Still, it often leads to severe disability.…”
mentioning
confidence: 99%
“…Generally, abnormalities higher on the spine produce a greater risk of paralysis and other debilitating complications. [53][54][55][56][57] Nowadays, all women are advised to take a supplement of 400 mg of folic acid for at least 3 months before preg nancy and up to the end of the 12th week of pregnancy. 58 Women who have a family history of NTDs are advised to take a higher dose of 5 mg of folic acid, as this has been shown to reduce their chances or having another baby with an NTD.…”
mentioning
confidence: 99%